In vitro nematicidal effect of endophytic Fusarium oxysporum against Radopholus similis, Pratylenchus goodeyi and Helicotylenchus multicinctus - Dessel, P. van; Coyne, Danny L.; Dubois, T.; Waele, D. de; Franco, J. (2011)
Endophytic fungi colonize most plants, causing no damage to their hosts, and often extending benefits, such as enhanced protection against various biotic and abiotic constraints. In the current study, three experiments assessed the activity of secondary metabolites of three strains of endophytic Fusarium oxysporum (Emb2.4o, Eny1.31i and V5w2) against the banana (Musa spp.) root-parasitic nematodes Radopholus similis, Pratylenchus goodeyi and Helicotylenchus multicinctus under different laboratory procedures. All experiments showed higher nematode mortality after 24 h exposure for each endophyte culture filtrate compared to control treatments after 24 h exposure. Helicotylenchus multicinctus was less sensitive to endophytic treatments than R. similis and P. goodeyi; and R. similis was more sensitive than P. goodeyi to strain V5w2 even at lower filtrate concentrations. Based on motility of R. similis and P. goodeyi, light (14 L: 10 D h) had no significant effect on endophyte culture filtrates (Emb2.4o and V5w2). These results indicate the potential of endophytic F. oxysporum as an environmentally sensitive management strategy for a range of plant-parasitic nematodes on banana, although more detail is required on the identification of the toxic metabolites involved.